Phosphorus-based anode materials for alkali-ion batteries - Capone, I (2020)
The development of high energy density Li-ion batteries required for electric vehicle and portable device applications requires the advancement of electrode materials, specifically the increase of their specific capacity many-fold. Moreover, the high demand for these devices is likely to cause concerns, stemming from the geographical concentration and scarce availability of Li in the long term, which will likely result in an increase in cost of Li-ion batteries. Therefore, research toward technologies based on similar chemistries, such as Na-ion and K-ion has shown increasing popularity. Red phosphorus (RP) is a promising anode material because it can host all three alkali ions, and is also able to deliver a very high theoretical capacity of 2596 mAh/g for Li and Na and 865 mAh/g for K, compared to graphite with Li and K (372 mAh/g and 279 mAh/g, respectively). However, it suffers from poor electronic conductivity (10-14 S/cm) and, being an alloying material, also suffers from severe volume expansion/contraction upon cycling, which cause damage to the electrode material, leading to poor cycle life. In this thesis, I focus my attention on studying the properties of RP that could lead to the failure of the anode material. This study was first conducted at the particle level, where the mechanism of the alloying reaction was simulated by a computational model to understand the generation and development of stresses on the particle and the possibility that these could lead to its catastrophic failure. This was done by accurate measurement of the mechanical properties of RP, elastic and plastic, and the diffusivity of alkali ions in RP, provided here for the first time. Moreover, a study at the composite level of a RP-graphite electrode is provided. The effect of properties of the composite, such as the particle-size distribution of RP and the mixing time of RP with graphite were investigated, in order to optimize the synthesis of a composite that can achieve high capacity and long cycle life.